Disaster risk and its reduction: an agenda for urban Africa. Issue 1 (1st January 2015) - Adelekan, Ibidun; Johnson, Cassidy; Manda, Mtafu; Matyas, David; Mberu, Blessing U.; Parnell, Susan; Pelling, Mark; Satterthwaite, David; Vivekananda, Janani
Abstract: Populations and assets, in African cities, small and large, are among the most vulnerable to disaster risk globally. Climate change and demographic shifts add urgency and uncertainty. This paper outlines priorities for research responding to this challenge. We argue for integrative approaches that can capture multi-hazard risk and include hazards from across the spectrum of everyday to catastrophic, and their interactions. For such approaches to shape policy, new efforts are needed to develop political support, technical capacity and methodologies to enable systematic data collection and analysis, including socially and spatially disaggregated data. We also argue for the interdependence of risk and urban development policy, and a focus on institutions as objects and partners for co-produced research, including local government as the focal point for risk reduction and new roles for civil society and the private sector. This emerging research agenda also needs to ask what it is that makes African cities distinctive globally, and yet diverse across the continent, in their experiences of risk production.